La promoción de la eugenesia en México a inicios del siglo XX - Víctor Octavio Hernández Ávila (Eleuthera)
At the beginning of the twentieth century, the eugenics movement become popular in various parts of the world. Mexico, like many other Latin American countries, considered it appropriate to analyze the eugenic knowledge of the time and then apply it to the country’s population. eugenic knowledge of the time and then apply it to the country’s population. To achieve this, they considered that their main tool would be a scientific popularization magazine. The objective of this article is to analyze the main characteristics of the Eugenesia magazine and to link them with the direct effects it had on the promotion of eugenics in Mexico between 1930 and 1945, using a qualitative methodology, through a discourse analysis of the texts of the Eugenesia magazine. It was concluded that eugenics was easily promoted in Mexico, largely because of the racist and hierarchical logic that had been established in the country at that time, on the other hand, it kept the general characteristics of eugenics in other parts of the world, information was promoted without scientific support. information was promoted without scientific support.